2023
DOI: 10.1002/anie.202304957
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically‐Driven CO2 Release Using a Metastable‐State Photoacid for Energy Efficient Direct Air Capture

Uvinduni I. Premadasa,
Vera Bocharova,
Audrey R. Miles
et al.

Abstract: One of the grand challenges underlying current direct air capture (DAC) technologies relates to the intensive energy cost for sorbent regeneration and CO2 release, making the massive scale (GtCO2/year) deployment required to have a positive impact on climate change economically unfeasible. This challenge underscores the critical need to develop new DAC processes with substantially reduced regeneration energies. Here, we report a photochemically‐driven approach for CO2 release by exploiting the unique propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Photoisomerization represents the first step in the complex photoreaction of an mPAH, a novel class of photoacid capable of producing a large proton concentration with high efficiency, good reversibility, and an extremely long-lived acidic state with a half-life ranging from seconds to hours. 1–3 The mPAHs have enabled the successful demonstration of various chemical, energy, materials, and biomedical applications, such as photochemically-driven CO 2 release 4,5 and dissipative assembly. 2,6 While multiple isomers with various connected pathways during a photoreaction cycle are often considered to promote their unique functionalities, the transient intermediates and associated structural dynamics of mPAHs remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photoisomerization represents the first step in the complex photoreaction of an mPAH, a novel class of photoacid capable of producing a large proton concentration with high efficiency, good reversibility, and an extremely long-lived acidic state with a half-life ranging from seconds to hours. 1–3 The mPAHs have enabled the successful demonstration of various chemical, energy, materials, and biomedical applications, such as photochemically-driven CO 2 release 4,5 and dissipative assembly. 2,6 While multiple isomers with various connected pathways during a photoreaction cycle are often considered to promote their unique functionalities, the transient intermediates and associated structural dynamics of mPAHs remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear if the early time dynamics identified for a merocyanine photoacid would occur in an indazole photoacid, a different type of mPAH that has attracted much attention in recent years. 1,5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated photoacid-triggered formation of carbonic acid for spectroscopic characterization and photoacid-accelerated CO 2 release from acidic conditions . Very recently, an elegant strategy using an indazole photoacid to promote CO 2 release from amino acid sorbents was also reported . However, identification of a single-component solute that can recurrently capture and release according to dark/light cycles remains a highly desirable goal.…”
Section: Introductionmentioning
confidence: 99%
“…24 Very recently, an elegant strategy using an indazole photoacid to promote CO 2 release from amino acid sorbents was also reported. 25 However, identification of a single-component solute that can recurrently capture and release according to dark/light cycles remains a highly desirable goal. Further, a systematic framework for analyzing the thermodynamic requirements and experimental investigation of the precise mechanism of the photochemical process is needed to provide a theoretical foundation for the development of this novel approach to reversible carbon capture.…”
Section: ■ Introductionmentioning
confidence: 99%